Towards sustainable water management in Morocco: assessing resources, challenges, and adaptation strategies - Boutagayout, Abdellatif; Hamdani, Anas; Boutgayout, Ismail; Adiba, Atman (Frontiers in Sustainable Food Systems, 2025)
Water management in Morocco has become a central challenge at the intersection of climate variability, agricultural modernization, and resource governance. The country is increasingly confronted with extreme hydro-climatic conditions that threaten water security and food production. Recent years have illustrated the severity of this crisis: 2023 was the driest year in at least eight decades, with total rainfall below 100 mm and a deficit of nearly 48% compared to the national average. The six-year period from 2019 to 2024 represents the longest recorded sequence of consecutive drought years, with an average rainfall deficit of 35%. Despite a progressive increase in hydraulic infrastructure, rising from a storage capacity of 1.2 billion m3 in 1960 to more than 19 billion m3 today, reservoirs were only 28.5% full in 2024, storing 4.8 billion m3. This structural water deficit is particularly concerning given that nearly 80% of Morocco’s cultivated land relies on rain-fed agriculture, making the agricultural sector vulnerable to fluctuating precipitation and rising temperatures. Morocco has attempted to address these challenges through ambitious policy frameworks, which prioritize efficient irrigation systems, sustainable agricultural practices, and resilience to climatic shocks. Large-scale investments in dams, desalination, and irrigation modernization have been complemented by international partnerships that provide technical expertise and financial support to the country. Simultaneously, agroecological practices, such as agroforestry, crop diversification, and crop rotation, represent underutilized but highly relevant pathways for improving water efficiency, restoring soil fertility, reducing erosion, and enhancing biodiversity. By weaving together climatic evidence, hydrological data, and agricultural strategies, this review highlights the urgency of implementing integrated water governance in Morocco. This underscores the importance of combining technological innovation with ecological practices and policy reforms to secure water and food resources in a context marked by persistent droughts and accelerating climate change.